Purchasing Power Parity: A ‘must have’ tool in a multinational enterprise’s toolbox - Bohlouli Ghashghaee, Bijan (2013)
Multinational corporations (such as E.ON) are exposed to foreign exchange risk due to the nature of their business model (operations outside their home country). The extent of the exposure has proved to be significant over time as expected and unexpected fluctuations in bilateral exchange rates affect their cash flows, earnings and their market value (as perceived by markets). In addition to that, multinational firms’ competitiveness in overseas markets are also strongly influenced by exchange rate movements as adverse movements in exchange rates may lead to the loss of competitive advantage (and vice versa) in targeted overseas markets. In order to limit the uncertainty caused by the volatility of bilateral exchange rates in foreign exchange markets, MNCs tend to adopt various hedging strategies (financial hedging is known to be one of the most commonly adopted strategies of minimizing the foreign exchange exposure). The use of currency derivatives (financial hedging instruments) could mitigate MNC’s exposure to the FOREX but it may prove to be costly and destructive if used blindly since the complexity of these financial hedging derivatives have raised so much that made them hard to understand. MNCs participation in currency derivatives markets is encouraged BUT WITH EXTRA CARE AND KNOWLEDGE. Purchasing Power Parity is amongst the theories that could provide a fairly reasonable insight into the foreign exchange markets. This theory suggests that over a long horizon the bilateral exchange rates should move to offset the effect of the inflation rate differentials between the countries of interest. I have tested to see if PPP holds between Sterling and Euro over the period of (January 2000 to July 2013) and found satisfactory results and therefore suggested that MNCs should consider using PPP as a tool that can direct them in formulating their hedging strategies and their overseas capital budgeting decisions.